Detection of Free Sugars in Almond Genotypes from Eastern and Western Turkey by HPLC - FIKRET BALTA, M.; YORUK, I.H.; KAZANKAYA, A.; BATTAL, P. (Asian Journal of Chemistry, 2010)
This study evaluated the sugar contents in almond [Prunus dulcis (Mill.) D.A. Webb.] genotypes, depending on their kernel sizes and kernel colours. Based on small kernel (SK) and large kernels (LK), sugar contents were compared both in sweet kernelled almond genotypes from Balikesir (western Anatolia, Turkey) and in bitter kernelled almond genotypes from Tunceli (eastern Anatolia, Turkey). Sugar contents were detected by HPLC. In all sweet and bitter LK and SK genotypes, contents of sucrose, maltose, glucose and fructose did not differ statistically except for only fructose content in bitter almonds. The LK and SK sweet genotypes contained 2.14-2.79 g/100 g sucrose, 0.61-0.44 g/100 g maltose, 1.20-2.05 g/100 g glucose and 3.28-3.45 g/100 g fructose, respectively. The LK and SK bitter genotypes contained 3.08-1.80 g/100 g sucrose, 0.85-1.34 g/100 g maltose, 2.28-2.38 g/100 g glucose and 3.67-2.73 g/100 g fructose, respectively. On the other hand, sugar contents were also compared based on light coloured kernel (LCK) and dark coloured kernel (DCK) in sweet and bitter genotypes. In sweet genotypes, sucrose, maltose and glucose contents of LCK and DCK did not differ statistically. In bitter genotypes, sucrose and glucose contents of LCK and DCK differed statistically. The sweet LCK and DCK genotypes contained 2.36-2.10 g/100 g sucrose, 0.60-0.74 g/100 g maltose, 1.58-2.32 g/100 g glucose and 3.28-2.56 g/100 g fructose, respectively. The bitter LCK and DCK genotypes contained 3.73-2.05 g/100 g sucrose, 1.10-1.36 g/100 g maltose, 3.56- 1.56 g/100 g glucose and 2.63-4.05 g/100 g fructose, respectively. In addition, the mean sugar was usually fructose in LK, SK, LCK and DCK.